Influence of trait anxiety, child maltreatment, and adulthood life events on depressive symptoms - Uchida Y (Dove Medical Press, 2018)
Yoshihiro Uchida,1–3 Toshinao Takahashi,1,3 Shigemasa Katayama,1,3 Jiro Masuya,1,2 Masahiko Ichiki,1 Hajime Tanabe,4 Ichiro Kusumi,5 Takeshi Inoue1 1Department of Psychiatry, Tokyo Medical University, Shinjuku-ku, Tokyo 160-0023, Japan; 2Department of Psychiatry, Ibaraki Medical Center, Tokyo Medical University, Ami-machi, Inashiki-gun, Ibaraki 300-0395, Japan; 3Department of Psychiatry, Seijin Hopital, Adachi-ku, Tokyo 121-0815, Japan; 4Department of Clinical Human Sciences, Graduate School of Humanities and Social Sciences, Shizuoka University, Suruga-ku, Shizuoka 422-8529, Japan; 5Department of Psychiatry, Hokkaido University Graduate School of Medicine, Kita-ku, Sapporo 060-8638, Japan Background: Various personality traits mediate the association between childhood stress and depressive symptoms in adulthood. The aim of this study was to clarify the indirect effects of the experience of child maltreatment on depressive symptoms and appraisal of life events in adulthood through trait anxiety. Subjects and methods: A total of 404 participants who were volunteer subjects from the community were studied using the following self-administered questionnaire surveys: Patient Health Questionnaire-9, which measures depressive symptoms; State-Trait Anxiety Inventory Form Y, which measures trait anxiety; the Child Abuse and Trauma Scale, which measures child maltreatment; and Life Experiences Survey, which measures negative and positive appraisal of adulthood life events. Results: Structural equation modeling demonstrated that the experience of child maltreatment increased depressive symptoms in adulthood as well as the negative appraisal of life events in adulthood through an increase in trait anxiety. Furthermore, trait anxiety affected depressive symptoms in adulthood through its influence on the negative appraisal of adulthood life events. The following indirect effect was also significant: the experience of child maltreatment increased the negative appraisal of adulthood life events via trait anxiety and subsequently influenced adult depressive symptoms. Limitations: The subjects of this study are volunteer subjects from the community including healthy people, and hence the results may not be generalizable to major depressive patients. Recall bias should be considered when interpreting the results. Because this study is a cross-sectional study, the causality between the experience of child maltreatment and depression is not clear. Conclusion: This study suggests that trait anxiety may play a mediating role in the influence of the experience of child maltreatment on depressive symptoms in adulthood and negative appraisal of adulthood life events. Keywords: child maltreatment, covariance structure analysis, depression, STAI-Y, trait anxiety, life events